Xylene isomerization in a membrane reactor. Part I: The synthesis of MFI membranes for the p-xylene separation - Tarditi, Ana Maria (2006)
The synthesis and characterization of silicalite and ZSM-5 films supported on porous SS tubes are described. Composite membranes were used to separate xylene isomers between 150 and 400 °C. Permeation measurements of the individual isomers and the ternary mixture were performed at each temperature within this interval. N2 permeation measurements together with SEM observations were used to determine whether or not cracks and/or pinholes developed after exposure to the xylene isomers at high temperature. The ZSM-5 membrane was superior to the silicalite one because of its higher permeance flux (1.16 × 10-5 mol s-1 m-2), separation factors (p/o 4.4), and up to 400 °C stability.